Performance Analysis and Investigation of the Slipstream Flow of Podded Propellers - Arikan, Yasemin; Dogrul, Ali; Celik, Fahri (BRODARSKI INST, 2012)
Especially high speed craft (HSC) and vessels with large propellers have unfavourable effects on the marine environment. These effects are mostly observed on other vessels and on the marine life. The most important sources of these negative effects caused by ships are the propeller slipstream flow and the ship wake. Marine propellers in particular can create a large effect area by accelerating the flow behind the ship, so they can cause erosion on coastal structures and on the sea bed while they traverse narrow channels and straits. In this study the effects of the propeller slipstream on the marine environment are analyzed for a model propeller and a podded propeller of a RO-RO ship by a computational fluid dynamics method. The validations of the numerical results are made through the comparison with the experimental results. The numerical predictions of the propeller slipstream flows are important for obtaining results which cannot be acquired by experimental measurements. The computations are made separately for the open water and behind the hull conditions for the podded propeller. Additionally, the propeller characteristics for the model and the podded propeller are calculated for various advance coefficients.
Keywords: CFD; marine propellers; model experiment; t-pod; propeller slipstream; Engineering